Evolution of phase composition and microstructure of commercial Al2O3 gel in different heat treatment condition. Issue 7 (May 2018) - Wang, Yuping; Liu, Xinhong; Chen, Xiaoyu; Wen, Yubin; Jia, Quanli
Abstract: Evolutions of phase composition and microstructure of commercial Al2 O3 gel in different heat treatment conditions (temperature, atmosphere and additives) were investigated. There was almost no effect of atmosphere and carbon additive on phase evolution of Al2 O3 gel during heating, γ-Al2 O3 formed at 800 °C, γ-Al2 O3 and minor θ-Al2 O3 co-existed at 1000 °C, and single phase of ɑ-Al2 O3 occurred at heating temperature ≥1200 °C. Atmosphere and carbon had great effects on morphology and crystal size of Al2 O3 particles. Crystal size of spherical-shape Al2 O3 particles was 10–20 nm after heating at 800–1000 °C in air, afterwards, they rapidly grew into micro or macro scale when temperature was above 1200 °C, and sintering phenomena of worm-like Al2 O3 particles were observed. In the presence of carbon, spherical-shape Al2 O3 particles grew slightly from 10 to 20 nm to 50–60 nm with the temperature increasing from 800 °C to 1500 °C in reducing atmosphere, carbon inclusions in Al2 O3 grain boundaries triggered a steric hindrance of Al2 O3 particles growth. Al2 O3 gel had a high reactive ability and could react with microsilica to form nano mullite crystals at relatively lower temperature.